Protective Effects of Vitamin C, Vitamin E, and Levamisole on the Lead-induced Thrombocytopenia in Male Wistar Rats - , B. J Olatunde; , S.O Ojeka; , D.V Dapper (Archives of Current Research International, 2024)
Aim: The study was undertaken to investigate the protective effects of selected antioxidants on lead-induced thrombocytopenia, using male Wistar rats as experimental models. Methodology: One hundred and sixty-two male Wistar rats with weight between 180 and 200 g were obtained from the Experimental Animal Farm of the University of Port Harcourt, Nigeria. The Wistar rats were housed in animal wooden cages in a well-ventilated experimental room and allowed to acclimatize for a period of two weeks before the commencement of treatments. The control group (group 1) was orally given 0.5ml of distilled water while the treatment groups (groups 2 to 9) were orally given different substances as follows: 10mg/Kg Body Weight (BW) of Lead only, 200mg/Kg BW of Vitamin C only, 1000iu/Kg BW of Vitamin E only, 10mg/Kg BW of Lead + 200mg/Kg BW of Vitamin C, 10mg/Kg BW of Lead + 1000iu/Kg BW of Vitamin E, 10mg/Kg BW of Lead + 40mg/BW Levamisole, 10mg/Kg BW of Lead + 200mg/Kg BW of Vitamin C + 40mg/BW Levamisole and 10mg/Kg BW of Lead + 1000iu/Kg BW of Vitamin E + 40mg/Body Weight Levamisole respectively once a day. The experiment was conducted in three phases (phases 1 to 3), which lasted for 7 days (acute phase), 30 days (sub-acute phase) and 60 days (chronic phase). At the expiration of the experimentation for each phase, five (5) rats were sacrificed blood samples were collected from each rat and examined for thrombocyte parameters. The effects of treatment with lead and antioxidants were compared with the control group. Results: There was a significant decrease in the concentrations of Plateletocrit (PCT) and Platelet count (PLT) and a significant decrease in Mean platelet volume (MPV), Platelet distribution width (PDW), Platelet large cell ratio (PLCR) and Platelet large cell count (PLCC) all in group 2, with respect to the control. There was also a significant increase in PLT in the lead group with respect to the control, in all the phases. Also, there was a significant increase in the concentrations of PCT (in groups 5, 6, 8 and 9) and PLT (in groups 5, 8, 9), all with respect to the lead group. Finally, there was a significant decrease in the concentrations of MPV (in groups 5 to 9), PDW (in groups 5 to 9), PLCR (in group 5 to 8) and PLCC (in group 9), all with respect to the lead group. Conclusion: Our study has demonstrated the ability of Vitamin C, Vitamin E, and Levamisole to protect lead-induced Toxicity on the platelet parameters.